Education Expenditure and Economic Growth in Mauritius: An Application of the Bounds Testing Approach - Sunde, Tafirenyika (European Scientific Journal, ESJ, 2017)
This study examines the relationship between education expenditure and economic growth in Mauritius. The study employed the ARDL bounds testing methodology for the period 1976 to 2016. The study found that education expenditure Granger causes economic growth in Mauritius in the short run. In addition, the study also found that economic growth does not Granger cause education expenditure in Mauritius in the short run. However, in the long-run, the study found that there are long run relationships between education expenditure and economic growth in both equations; and this means that an increase in either of the variables will eventually lead to an increase in the other variable. The study, therefore, found support for the hypothesis that investment in education raises economic growth. This means that Mauritius has the potential to benefit from further investments in education in the future.